OXYGEN THERMOBAROMETRY OF ABYSSAL SPINEL PERIDOTITES - THE REDOX STATE AND C-O-H VOLATILE COMPOSITION OF THE EARTHS SUB-OCEANIC UPPER MANTLE - Bryndzia, L; Wood, B (1990)
We have applied the spinel peridotite oxygen barometer to abyssal spinel peridotites from the mid-Atlantic, central Indian, southwest Indian and American-Antarctic ocean ridge systems. The results indicate that the oxygen fugacity (fO2) of the suboceanic mantle is on average 0.9 ± 0.7 (n = 33; ± 1sd) log units below the Fayalite-Magnetite-Quartz (FMQ) fO2 buffer. Suboceanic mantle is more reduced than the subcontinental mantle. -from Authors